Pengaruh Lingkungan Kerja Dan Budaya Kerja Terhadap Kinerja Guru Dan Pegawai Pada Smp Negeri 1 Tebing Tinggi Kabupaten Empat Lawang - Gunawan, Gunawan (MOTIVASI, 2020)
Purpose – This study aims to determine how much influence the work environment has on the performance of teachers and employees at SMP Negeri 1 Tebing Tinggi, Empat Lawang Regency.Design/methodology – This research uses the Accidental sampling method, namely sampling which is done by chance by distributing questionnaires to Muara Siban gas station customers, Lahat District, Lahat Regency. Data collection is done when the customer is buying fuel at the gas station. The research will be carried out at Muara Siban Lahat SPBU. The research used is a quantitative approach. Through this research, it can be used as input for managers of Muara Siban gas stations.Findings - Esting the effect of work environment variables (X1) on performance, the tcount value of the work environment (X1) is -1.068 with a significant level of 0.294, then accepting Ho and rejecting Hi shows an insignificant influence between the work environment (X1) on performance (Y ). And the results of testing the influence of work culture variables (X2) on the performance (Y) of teachers and employees at SMP Negeri 1 Tebing Tinggi, Empat Lawang Regency, obtained that the tcount of work culture (X2) is 7,965 with a significant level of 0,000, so Ho rejects and accepts Hi. shows that there is a significant influence between work culture (X2) on performance (Y). And the results of the F test obtained 90.072 by taking a significant level of 0.05, so with a significant level of 0.000, Ho is rejected and Hi is accepted. This means that it can be concluded that there is a linear relationship between the work environment (X1), work culture (X2), together with the performance variable (Y). and explain the influence of work environment (X1), work culture (X2), together on performance variables (Y).